Emerging roles for IL-6 family cytokines as positive and negative regulators of ectopic lymphoid structures. (October 2021) - Hill, David G.; Ward, Amy; Nicholson, Lindsay B.; Jones, Gareth W.
Highlights: Ectopic lymphoid structures (ELS) are a hallmark of chronic tissue inflammation. ELS are inducible sites that promote autoimmune and anti-tumour immune responses. The IL-6 cytokine family includes positive and negative regulators of ELS formation. IL-6 family cytokines are potential targets for immunotherapy in ELS-rich diseases. Abstract: IL-6 family cytokines display broad effects in haematopoietic and non-haematopoietic cells that regulate immune homeostasis, host defence, haematopoiesis, development, reproduction and wound healing. Dysregulation of these activities places this cytokine family as important mediators of autoimmunity, chronic inflammation and cancer. In this regard, ectopic lymphoid structures (ELS) are a pathological hallmark of many tissues affected by chronic disease. These inducible lymphoid aggregates form compartmentalised T cell and B cell zones, germinal centres, follicular dendritic cell networks and high endothelial venules, which are defining qualities of peripheral lymphoid organs. Accordingly, ELS can support local antigen-specific responses to self-antigens, alloantigens, pathogens and tumours. ELS often correlate with severe disease progression in autoimmune conditions, while tumour-associated ELS are associated with enhanced anti-tumour immunity and a favourable prognosis in cancer. Here, we discuss emerging roles for IL-6 family cytokines as regulators of ELS development, maintenance and activity and consider how modulation of these activities has the potential to aid the successful treatment of autoimmune conditions and cancers where ELS feature.